Cord Blood Cryopreservation with PEO-1500 - Ryazantsev, V. V.; Babijchuk, L. A.; Zubova, O. L.; Gurina, T. M. (Problems of Cryobiology and Cryomedicine, 2007)
The method without washing-out for the whole cord blood cryopreservation with PEO-1500, enabling to preserve up to 99 and 93% erythrocytes after freeze-thawing and by the transfusion test data, correspondingly, has been designed. The integrity of biologically active substances in plasm at the control level has been established. After cryopreservation with the mentioned above method the immunofluorescent test has demonstrated the integrity of up to 70% blood lymphocytes, including cord blood stem cells (CD34+).